Study of excited Lambda(0)(b) states decaying to Lambda(0)(b)pi(+)pi(-) in proton-proton collisions at root s=13TeV - Sirunyan, A. M. (2020)
A study of excited Lambda(0)(b) baryons is reported, based on a data sample collected in 2016-2018 with the CMS detector at the LHC in proton-proton collisions at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of up to 140fb(-1). The existence of four excited Lambda(0)(b) states: Lambda(0)(b) (5912)(0), Lambda(0)(b) (5920)(0), Lambda(0)(b) (6146)(0), and Lambda(0)(b) (6152)(0) in the Lambda(0)(b)pi(+)pi(-) mass spectrum is confirmed, and their masses are measured. The Lambda(0)(b)pi(+)pi(-) mass distribution exhibits a broad excess of events in the region of 6040-6100 MeV, whose origin cannot be discerned with the present data. (C) 2020 The Author(s). Published by Elsevier B.V.